Health-related quality of life of cancer patients undergoing radiotherapy - Juliana Maria de Paula; Namie Okino Sawada (Rev Rene)
Objective: to evaluate the health-related quality of life of patients with head and neck cancer during radiotherapy treatment. It was carried out with 41 patients between 2009-2010 in central radiotherapy. Methods: this is a longitudinal study. It was used the Functional Assessment Cancer Therapy Head and Neck. The predominance of cases were male, with a mean age of 62 years. Results: in the 5 domains assessed, the one that was more affected was the “physical well-being”, which is directly related to the side effects of treatment. Conclusion: the symptoms caused by the treatment are negatively associated with the Quality of Life Related to Health Care, so it is important that the health care team assess and identify the needs of the patient, allowing him to have a monitor that meets your needs and minimize symptoms.